Galois embedding problems and symmetric powers - Crespo, Teresa; Hajto, Zbigniew (MATHEMATICA SCANDINAVICA, 2005)
We consider a Galois embedding problem given by a finite projective group and its special linear lifting. We give an equivalent condition to the solvability of such an embedding problem and a method of construction of its solutions.